2017
DOI: 10.1111/vec.12639
|View full text |Cite
|
Sign up to set email alerts
|

Necroulcerative hemorrhagic gastritis in a cat secondary to the administration of 3% hydrogen peroxide as an emetic agent

Abstract: The oral administration of 3% hydrogen peroxide solution in cats can result in necroulcerative gastritis as a possible sequel. While hydrogen peroxide is considered a safe emetic agent in dogs, its use in cats is not recommended. As a result, the use of emetic agents in cats should be limited to veterinary administration, using alternative, safer emetic agents such as alpha-adrenergic agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Veterinarians should be aware of the possibility of hemorrhagic necroulcerative gastritis after administration of this agent. 13 Endoscopy is an effective tool for the removal of objects from the gastrointestinal tract of cats and showed high success and low complication rates in the present study as a first-line treatment modality. 2 The cats in our paper were mostly older, and many had pre-existing medical conditions; therefore, avoiding a longer duration of anesthesia and surgical procedures may be beneficial.…”
Section: Discussionmentioning
confidence: 54%
“…Veterinarians should be aware of the possibility of hemorrhagic necroulcerative gastritis after administration of this agent. 13 Endoscopy is an effective tool for the removal of objects from the gastrointestinal tract of cats and showed high success and low complication rates in the present study as a first-line treatment modality. 2 The cats in our paper were mostly older, and many had pre-existing medical conditions; therefore, avoiding a longer duration of anesthesia and surgical procedures may be beneficial.…”
Section: Discussionmentioning
confidence: 54%
“…The use of 3% H 2 O 2 administration as an emetic is not recommended in cats, and there are no reports describing acute respiratory distress after its administration [24]. Oral administration of 3% H 2 O 2 solution in cats can result in necroulcerative gastritis as a sequela [3].…”
Section: Discussionmentioning
confidence: 99%
“…Irritation and inflammation of the mucous membrane in the pharynx, esophagus, and stomach, resulting from H 2 O 2 ingestion and pain should be considered as a possible cause of inappetence. Some articles have reported the risk of hemorrhagic and necroulcerative hemorrhagic gastritis following 3% H 2 O 2 administration as an emetic in cats; therefore, it is not recommended in this species [3, 6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other agents previously recommended to induce emesis that are no longer recommended include salt/salt water (as it can cause life‐threatening hypernatraemia), mustard, syrup of ipecac and hydrogen peroxide. Although hydrogen peroxide was shown to have minimal adverse effects in one retrospective study (Kahn and others 2012), a prospective experimental study found significant overt and histopathological gastric lesions in dogs after administration of 3 per cent hydrogen peroxide (Niedswecki and others 2017) and severe necroulcerative haemorrhagic gastritis has been described in a cat after its use (Obr and others 2017).…”
Section: Decontaminationmentioning
confidence: 99%